2016
DOI: 10.5539/jas.v8n9p12
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Lignin Structural Units and Soil Organic Carbon Content by Cowpea Peroxidase

Abstract: Peroxidases participate in lignin biosynthesis, but there is no biochemical resolution between the structural units of lignin and soil organic carbon (SOC) contents. Black-eyed beans are staple high-protein foods for millions of at-risk populations in every continent. Its cultivation in semiarid zones could be leveraged to maximize SOC sequestration. Cowpea was treated with stoichiometric mixes of mineral nutrients. Peroxidase was electrophoretically purified from leaves, and assayed for o-dianisidine (guaiacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…When the total protein content of cowpea seeds was low as in unfertilized control cowpea, it suggested that GDH synthesized the RNA enzyme fragment #5 ( Table 2) that partially degraded some of the mRNA encoding the vicilin [9]. Therefore, GDH through synthesis of RNA maintains a biochemical equilibrium between the plants' exterior environment and the interior biochemical, metabolic, physiological environment, as reflected by cowpea dry grain yield ( Table 2) that destroyed the mRNA encoding the peroxidases [73]. Therefore, inappropriate fertilization that caused decreases of soil organic carbon contents [7] led to decreases in cowpea dry grain yield (Table 1).…”
Section: Biochemical Pathways Of Gdh-synthesized Rna Enzymes In Cowpeasmentioning
confidence: 99%
“…When the total protein content of cowpea seeds was low as in unfertilized control cowpea, it suggested that GDH synthesized the RNA enzyme fragment #5 ( Table 2) that partially degraded some of the mRNA encoding the vicilin [9]. Therefore, GDH through synthesis of RNA maintains a biochemical equilibrium between the plants' exterior environment and the interior biochemical, metabolic, physiological environment, as reflected by cowpea dry grain yield ( Table 2) that destroyed the mRNA encoding the peroxidases [73]. Therefore, inappropriate fertilization that caused decreases of soil organic carbon contents [7] led to decreases in cowpea dry grain yield (Table 1).…”
Section: Biochemical Pathways Of Gdh-synthesized Rna Enzymes In Cowpeasmentioning
confidence: 99%